Active afforestation of drained peatlands is not a viable option under the EU Nature Restoration Law - Gerald Jurasinski; Alexandra Barthelmes; Kenneth A. Byrne; Bogdan H. Chojnicki; Jesper Riis Christiansen; Kris Decleer; Christian Fritz; Anke Beate Günther; Vytas Huth; Hans Joosten; Radosław Juszczak; Sari Juutinen; et al. (Ambio, 2024)
The EU Nature Restoration Law (NRL) is critical for the restoration of degraded ecosystems and active afforestation of degraded peatlands has been suggested as a restoration measure under the NRL. Here, we discuss the current state of scientific evidence on the climate mitigation effects of peatlands under forestry. Afforestation of drained peatlands without restoring their hydrology does not fully restore ecosystem functions. Evidence on long-term climate benefits is lacking and it is unclear whether CO 2 sequestration of forest on drained peatland can offset the carbon loss from the peat over the long-term. While afforestation may offer short-term gains in certain cases, it compromises the sustainability of peatland carbon storage. Thus, active afforestation of drained peatlands is not a viable option for climate mitigation under the EU Nature Restoration Law and might even impede future rewetting/restoration efforts. Instead, restoring hydrological conditions through rewetting is crucial for effective peatland restoration.

Moult and mobility of the Aquatic Warbler Acrocephalus paludicola on the West African non-breeding grounds - Cosima Tegetmeyer; Marco Thoma; Susanne Arbeiter (Journal of Ornithology, 2012)

Distribution, ecology and threat status of the Aquatic Warblers Acrocephalus paludicola wintering in West Africa - Martin Flade; Ibrahima Diop; Martin Haase; Arnaud Le Nevé; Steffen Oppel; Cosima Tegetmeyer; Anna Vogel; Volker Salewski (Journal of Ornithology, 2011)